Bottlebrush compatibilizers with polythiophene backbones and dielectric/conductive side brushes in naphthothiadiazole solar systems. (December 2019) - Jia, Anqiang; Liu, Haiyan; Yun, Yingxia; Agbolaghi, Samira
Graphical abstract: Highlights: P3ThEt- g -PSt and P3ThEt- g -PANI bottlebrushes were morphology compatibilizers. A 20wt% of bottlebrushes was optimal and PCEs of 5.34 and 5.26% were detected. PBDT-DTNT based devices were better than the PBDT-TIPS-DTNT-DT based ones. Donor and acceptor phase regions were modified by the compatibilizers. Abstract: Poly(3-thiophene ethanol) (P3ThEt)- g -polystyrene (PSt) and P3ThEt- g -polyaniline (PANI) bottlebrushes were used as morphology compatibilizers in poly[benzodithiophene-bis(decyltetradecyl-thien) naphthothiadiazole] (PBDT-DTNT):phenyl-C61-butyric acid methyl ester (PC61 BM) and poly[bis(triiso-propylsilylethynyl) benzodithiophene-bis(decyltetradecyl-thien) naphthobisthiadiazole] (PBDT-TIPS-DTNT-DT):PC61 BM photovoltaics. Although 10 wt% of P3ThEt- g -PSt and P3ThEt- g -PANI bottlebrushes improved the cell features (4.39–4.42% versus 3.24%), a 20 wt% was found to be the optimal compatibilizer content and performances of 5.34 and 5.26% were detected, respectively. Polythiophenic backbones covered with either coily PSt brushes or rod PANI brushes enabled the simultaneous growth of donor and acceptor assemblies in these systems. Therefore, the hole (4.6 × 10 −3 and 4.9 × 10 −3 cm 2 /V·s) and electron (5.1 × 10 −2 and 5.5 × 10 −2 cm 2 /V·s) mobilities and also other photovoltaic properties (12.68 and 12.71 mA/cm 2 ; 61 and 60%; 0.69 and 0.69 V) were improved. In contrast, PBDT-TIPS-DTNT-DT based devices did not benefit from bottlebrush compatibilizers as much as PBDT-DTNT based ones and performance peaked at 3.81% for PBDT-TIPS-DTNT-DT:PC61 BM:10 wt% P3ThEt- g -PSt system. Herein, addition of rod-coil and rod-rod bottlebrushes further affected PC61 BM clustering than polymer crystallization with complicated structures and TIPS side groups. Only 10 wt% of bottlebrushes, especially rod-coil P3ThEt- g -PSt ones, was enough in regulating the PCBM molecules and enhancing cell parameters. Thereafter, further raising the compatibilizer population saturated the active layer and, consequently, device functions especially hole mobility plummeted. The smallest charge transfer resistances (Rtr ) also belonged to PBDT-DTNT:PC61 BM:20 wt% P3ThEt- g -PSt (=273 Ω·cm 2 ) and PBDT-DTNT:PC61 BM:20 wt% P3ThEt- g -PANI (=276 Ω·cm 2 ). In optimum PBDT-DTNT:PC61 BM and PBDT-TIPS-DTNT-DT:PC61 BM systems, the recombination time values ranged in 18.3–18.4 ns and 12.1–14.8 ns, respectively.